Franchise Agreement as Legal Protection For Franchise Business Actors In Indonesia - Brun Kartino Sudjanto; Gunawan Djajaputra (Return : Study of Management, Economic and Bussines, 2024)
Franchise agreements play an important role in providing legal protection for franchise business actors in Indonesia, both for franchisors and franchisees. This study aims to analyze the effectiveness of franchise agreements in protecting the rights and obligations of the parties and identify potential legal problems that arise in their implementation. The approach used is normative juridical, with an analysis of related laws and regulations, such as Government Regulation No. 42 of 2007 concerning Franchises, as well as franchise agreement documents from various business sectors. The results of the study show that franchise agreements that are drafted by fulfilling the legal principles of the agreement, such as legal certainty, fairness, and balance, are able to provide adequate legal protection for both parties. However, there are still challenges in implementation, including inconsistencies in the content of the agreement with regulations, lack of understanding of legal aspects by business actors, and weak supervision of the implementation of the agreement. This research recommends strengthening regulations and education for franchise business actors to create a fairer and more sustainable business ecosystem.